Investigation Of Athletes Organizational Citizenship Behavior - Ekmekci, Ridvan; Orhan, Sumeyra (European Scientific Journal, ESJ, 2016)
The aim of this study was to examine the organizational citizenship behavior of active licensed athletes. Organizational citizenship includes altruism, conscientiousness, courtesy, sportsmanship and civic virtue as it was examined in five sections. These dimensions contribute to individual and organizational performance. 422 athletes participated in the study. The mean age of participants was found as 23,3. 265 men, 157 women participated to study. Consisting of 19 substances adapted into Turkish by H.Nejat BASIM "Organizational Citizenship Behavior Scale" was applied to the athletes. The reliability coefficient of the questionnaire (Cronbach’s alpha) was calculated as .85. Research statistics measured by mean, percentage and standard deviation. Independed t test and ANOVA analysis carried to testing group variances. Athletes’ organizational citizenship behavior mean level was generally high. This situation shows that the students who has organizational citizenship attitude which is defined as individual behavior based on volunteering has high organizational dependency in terms of themselves and their organizations and they are in condition that they consider the organization and its worker in the unwritten rules.